Microeconomics for managers - Kreps, David M. (Princeton Princeton University Press, 2019)
This is a thoroughly revised and substantially streamlined new edition of a leading textbook that shows MBA students how understanding economics can help them make smarter and better-informed real-world management decisions. David Kreps, one of the world$1 (Bs most influential economists, has developed and refined Microeconomics for Managers over decades of teaching at Stanford$1 (Bs Graduate School of Business. Stressing game theory and strategic thinking and driven by in-depth, integrated case studies, the book shows future managers how economics can provide practical answers to critical business problems.s